1991
DOI: 10.1002/jsfa.2740550410
|View full text |Cite
|
Sign up to set email alerts
|

Post‐mortem tenderisation of rainbow trout (Oncorhyncus Mykiss) muscle caused by gradual disintegration of the extracellular matrix structure

Abstract: A histological study combined with a newly devised compression test was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 19 publications
2
77
0
Order By: Relevance
“…On the other hand, Azam et al (1989) who studied the killing method effect on rainbow trout quality during storage on ice also observed a similar significant softening of both raw and cooked fillets during storage using instrumental measurement (Steven's Compression Response Analyzer, SCRA) method. This was further confirmed by Ando et al (1991) in addition to similar observations being made also by Hatae et al (1985) who reported a softening of the texture in several fish species stored at 4°C using General Foods (GF) texturometer. Changes in cohesiveness, springiness and chewiness: Cohesiveness being the ratio of work done during the second compression divided by work done during the first compression is an indication of the materials' viscoelasticity.…”
Section: Texture Analysissupporting
confidence: 81%
“…On the other hand, Azam et al (1989) who studied the killing method effect on rainbow trout quality during storage on ice also observed a similar significant softening of both raw and cooked fillets during storage using instrumental measurement (Steven's Compression Response Analyzer, SCRA) method. This was further confirmed by Ando et al (1991) in addition to similar observations being made also by Hatae et al (1985) who reported a softening of the texture in several fish species stored at 4°C using General Foods (GF) texturometer. Changes in cohesiveness, springiness and chewiness: Cohesiveness being the ratio of work done during the second compression divided by work done during the first compression is an indication of the materials' viscoelasticity.…”
Section: Texture Analysissupporting
confidence: 81%
“…Hallett and Bremner (1988) found, by using transmission electron microscope (TEM), that the majority of muscle Ðbres in blue grenadier were more or less completely detached after 11 days storage on ice. This disintegration is probably due to proteases attacking the type of collagen found in the perimysial Ðbrils (Bremner and Hallett 1985 ;Ando et al 1991 ;Sato et al 1991). Montero and Borderias (1990) found that the enzyme activity increased considerably post-rigor (72 h after death) whereas Nilsson and Ekstrand (1993) showed that ice storage for 14 days induced enzyme leakage from muscle tissue of rainbow trout, although not as much as in frozen samples.…”
Section: Results and Discussion E †Ects Of Dietmentioning
confidence: 96%
“…Collagen Ðbrils in connective tissue maintain toughness and the integrity of the Ðsh muscle and has been demonstrated to have an important role for Ðsh meat texture (Bremner and Hallett 1986 ;Love 1988 ;Ando et al 1991 ;Sato et al 1991). The muscle blocks (myotomes) 347 are separated by connective tissue (myocommata) which is mainly composed of collagen Ðbres.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[2][3][4][5][6] However, an understanding of the exact mechanisms involved in these changes, particularly in fish muscle, has not reached general agreement. …”
mentioning
confidence: 99%